Lead and Chromium Immobilization Process Subjected to Different Freeze-Thaw Treatments in Soils of the Northeastern Qinghai-Tibet Plateau - Leiming Li; Jun Wu (Journal of Chemistry)
The freeze-thaw cycle is one of the important processes that affected heavy metal behaviors in soil. However, information regarding the adsorption and desorption behavior of heavy metals in soils under different freeze-thaw conditions is relatively less. Therefore, different freeze-thaw conditions including unfrozen, 15 freeze-thaw cycles at 60% water content, and 15 freeze-thaw cycles at 100% water content were investigated. Then the adsorption and desorption behaviors of Pb and Cr in freeze-thaw soils were studied. Results showed the Pb and Cr adsorption amount mostly decreased with increasing water-soil ratio, and the soil performance of Pb and Cr adsorption at same water-soil ratios showed variation under different freeze-thaw conditions. The Pb isothermal adsorption was higher for most freeze-thaw treatments compared to the control. The soil performance of Cr isothermal adsorption showed variation under different freeze-thaw conditions. Most electrostatic binding of Pb and Cr were stronger under unfrozen and freeze-thaw conditions than unfrozen conditions. Most Pb and Cr adsorption kinetics patterns of freeze-thaw treated soils were rapid than unfrozen conditions. These results implied that freeze-thaw cycles could change the soil adsorption and desorption patterns of Pb and Cr. Therefore, further studies are urgently needed to investigate Pb and Cr immobilization mechanisms in soils during freeze-thaw cycles. Hence, these findings provided useful information on Pb and Cr immobilization process in soils that underwent freeze-thaw cycles to offer an additional insight into predicting Pb and Cr behaviors in cold and freezing environments.